MAIN REGULARITIES OF FAULTING IN LITHOSPHERE AND THEIR APPLICATION (BASED ON PHYSICAL MODELLING RESULTS) - S. A. Bornyakov; K. Zh. Seminsky; V. Yu. Buddo; A. I. Miroshnichenko; A. V. Cheremnykh; A. S. Cheremnykh; A. A. Tarasova (Геодинамика и тектонофизика)
Results of long-term experimental studies and modelling of faulting are briefly reviewed, and research methods and the-state-of-art issues are described. The article presents the main results of faulting modelling with the use of non-transparent elasto-viscous plastic and optically active models. An area of active dynamic influence of fault (AADIF) is the term introduced to characterise a fault as a 3D geological body. It is shown that AADIF's width (М) is determined by thickness of the layer wherein a fault occurs (Н), its viscosity (η) and strain rate (V). Multiple correlation equations are proposed to show relationships between AADIF's width (М), H, η and V for faults of various morphological and genetic types. The irregularity of AADIF in time and space is characterised in view of staged formation of the internal fault structure of such areas and geometric and dynamic parameters of AADIF which are changeable along the fault strike. The authors pioneered in application of the open system conception to find explanations of regularities of structure formation in AADIFs. It is shown that faulting is a synergistic process of continuous changes of structural levels of strain, which differ in manifestation of specific self-similar fractures of various scales. Such levels are changeable due to self-organization processes of fracture systems. Fracture dissipative structures (FDS) is the term introduced to describe systems of fractures that are subject to self-organization. It is proposed to consider informational entropy and fractal dimensions in order to reveal FDS in AADIF. Studied are relationships between structure formation in AADIF and accompanying processes, such as acoustic emission and terrain development above zones wherein faulting takes place. Optically active elastic models were designed to simulate the stress-and-strain state of AADIF of main standard types of fault jointing zones and their analogues in nature, and modelling results are reported in the article. A good correlation is revealed between the available seismological, structural geological and geodetic data.